Dynamics of broadbands demand: Substitution or complementarity between fixed and mobile technologies? An application to the Portuguese case - Rita Filipe Silva; Isabel Proença; Jo\~ao Vareda (International Telecommunications Society (ITS), 2013)
The development of the broadband market is a key aspect of the economic and social growth of a country. However, despite the importance and the development of broadband market in Portugal in recent years, especially with the explosion of the number of mobile broadband accesses, the studies for the Portuguese case are rare. The present paper seeks to contribute to the discussion about the definition of the broadband market in Portugal, specifically studying the demand for broadband Internet and measuring the determinants that explain the use of each of the technologies available to provide broadband access, with emphasis on the differences between fixed and mobile accesses. Demand broadband functions were estimated using nested logit and multinomial discrete choice model. The primary source of information was ANACOM's Electronic Communications Services Consumption Survey, complemented with price information regarding the offers available in the market. The estimations obtained for the elasticities point out the probable existence of substitution between ADSL and cable and between these fixed broadband technologies and the mobile broadband. However, the inverse relation is not statistically significant, the demand for mobile broadband isn't constrained by the price of ADSL or of cable, which may reveal the existence of asymmetric substitution between fixed and mobile broadband accesses. These results have implications in the definition of the broadband market in Portugal which will be discussed.
Keywords: L51; L96; 330; Broadband; Market Definition; Demand; Regulation; Fixed-Mobile Substitution